Night night! Sleep tight! - Mayer, Mercer, 1943- (Mayer, Mercer, 1943- Little Critter book., 2025)
"It's bedtime for Little Critter and Little Sister, but when there's a strange sound in the night, the two are determined to find the source of the tap-tap. Things that look like monsters in the dark turn out to be innocent in this nighttime adventure. Will they ever find out what's making the sound?"--Provided by publisher.